Religious Freedom Theology in Q.S. Al-Baqarah (2): 256 and Its Implications for Interfaith Harmony in North Sulawesi: Teologi Kebebasan Beragama dalam Q.S. Al-Baqarah: 256 dan Relevansinya Terhadap Harmoni Lintas Iman di Sulawesi Utara - Basri Saenong; Achmad Abubakar; Mardan Mardan (Takwil: Journal of Quran and Hadith Studies, 2025)
This article aims to analyze the principle of religious freedom in the Qur'an, focusing on Q.S. Al-Baqarah verse 256, and its relevance as a theological basis for interfaith harmony in North Sulawesi. This study uses a library research method with a qualitative-descriptive approach based on thematic interpretation (mauhdu'i).  The research data sources include primary data consisting of verses from the Qur'an, classical and contemporary interpretations. Sociological analysis is used as an interpretive approach, utilizing the theories of Peter L. Berger and José Casanova to examine the relationship between theological principles and social practices of diversity. The results of the study show that the verse "la ikraha fi al-din" is not merely an affirmation of freedom to choose a religion, but also a manifestation of spiritual freedom that underlies social harmony in a pluralistic society. In the context of North Sulawesi, the value of religious freedom is reflected through the practices of dialogue, tolerance, and cooperation among religious communities that flourish thanks to the local wisdom of mapalus as a symbol of communal solidarity. The findings of this study confirm that freedom of religion is not only related to theological aspects, but also functions as an instrument of social development, affirmation of national identity, and strengthening of humanitarian ethics in Indonesia's multicultural life.